HUBUNGAN MODEL PROGNOSTIK PASIEN CEDERA OTAK TRAUMATIK TERTUTUP SEDANG DAN BERAT DENGAN GOS 3 BULAN - Aida Fithrie*, Mursyid Bustami*, Yetty Ramli*, Joedo Prihartono** (NEURONA, 2010)
INTRODUCTION ESTABLISHING A RELIABLE PROGNOSIS EARLY AFTER INJURY IS NOTORIOUSLY DIFFICULTFOR ACCURATE OUTCOME PREDICTION MULTIPLE RISK FACTORS NEED TO BE CONSIDERED JOINTLY IN A PROGNOSTIC MODEL BECAUSE SINGLE FACTOR HAVE INSUFFICIENT PREDICTIVE VALUE TO DISTINGUISH PATIENTS WHO WILL DO WELL FROM THOSE WHO WILL DO POORLY